밸런싱 장치를 이용한 고속 주축 시스템의 능동 밸런싱에 관한 연구 - 김도형 (The Graduate School, Ajou University, 2005)
High speed spindle can be very sensitive to rotating mass unbalance that is a major source of harmful vibration for many machine tools. Mass unbalance occurs if the principle axis of inertia of the rotor is not coincident with its geometric axis. The effect of mass unbalance is a function of mass and speed squared. So, High speed causes more dangerous damage to the spindle, so the balancing procedure is needed for all high speed spindles. Most of the conducted balancing method is off-line balancing. But this way needs high-skilled technique, high-priced equipment and time consuming. Rotating machines like CNC machining center perform many auto-tool changing on the processing time, and it means that they need more balancing procedure for more accurate and faster works. Existing off-line balancing is not adequate to the balancing like that system. So, to save the time and cost of off-line balancing, a real-time active balancing method without stopping spindle is needed. This paper presents experimental balancing device and its control mthod for spindle of machining center. An electromagnetically actuate machine balancer including a plurality of peripherally placed magnetic circuits and power driver which selectively interrupts the magnetic flux through the circuits, thereby moving unbalanced rotors in a desired manner to compensate for machine unbalance.
학위논문(석사)--아주대학교 대학원 :기계공학과,2005